Nanoporous carbon from Cattial leaves for carbon dioxide capture. (2019) - Smuthkochorn, Araya; Katunyoo, Nardnutda; Kaewtrakulchai, Napat; Atong, Duangduen; Soongprasit, Kanit; Eiad-ua, Apiluck
Abstract: Reducing anthropogenic CO2 emissions and lowering the concentration of greenhouse gases in the atmosphere have quickly become one of the most urgent environmental issues of our age. Carbon capture and storage (CCS) is the option for reducing these harmful CO2 emissions. While a variety of technologies and methods have been developed, the separation of CO2 from gas streams is still a critical issue. Apart from establishing new techniques, the exploration of capture materials with high separation performance and low capital cost are of paramount importance. Nanoporous carbon derived from leaf of cattail flower that found in all areas throughout Thailand, the biomass was previously pyrolyzed at 500 to 700°C and the produced chars were further activated with NaOH, KOH, Na2 CO3 and K2 CO3 subsequently. Afterwards, the resulting materials were characterized by Scanning electron microscopy, Fourier-transform infrared spectroscopy and Raman scattering measurement. From this investigation, produced activated carbon will be efficient as an option for CO2 emission control.